2011
DOI: 10.4081/jphia.2011.e16
|View full text |Cite
|
Sign up to set email alerts
|

Genital mycoplasmas in women attending the Yaounde University Teaching Hospital, Cameroon

Abstract: Genital mycoplasmas are implicated in pelvic inflammatory diseases, puerperal infection, septic abortions, low birth weight, nongonococcal urethritis and prostatitis as well as spontaneous abortion and infertility in women. There is paucity of data on colonisation of genital mycoplasma in women and their drug sensitivity patterns. The aim of our study was to determine the prevalence of genital mycoplasmas (Ureaplasma urealiticum and Mycoplasma hominis) infection and their drug sensitivity patterns in women. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…The high rate of carriage of genital mycoplasmas in our study population is reminiscent of previous reports in women of reproductive age from neighboring countries, with prevalence rates of 65% in Cameroon [35] and 36% in Nigeria [36]. Genital mycoplasmas apart from M. genitalium (including M. hominis , U. parvum , and U. urealyticum ) are generally considered as commensals of the female uro-genital tract, as they may be found at rates up to 80% in sexually active women [37, 38].…”
Section: Discussionsupporting
confidence: 82%
“…The high rate of carriage of genital mycoplasmas in our study population is reminiscent of previous reports in women of reproductive age from neighboring countries, with prevalence rates of 65% in Cameroon [35] and 36% in Nigeria [36]. Genital mycoplasmas apart from M. genitalium (including M. hominis , U. parvum , and U. urealyticum ) are generally considered as commensals of the female uro-genital tract, as they may be found at rates up to 80% in sexually active women [37, 38].…”
Section: Discussionsupporting
confidence: 82%
“…Mycoplasmas are thus frequently isolated microorganisms from the genital tract of women,[30] but various prevalence rates of Mycoplasma and Ureaplasma infections have been reported. A study conducted in Cameroon revealed a prevalence of Mycoplasma at 48%,[31] and the Mycoplasma prevalence was evaluated at 42.8% in a study conducted in Korea. [32] Higher prevalence (80%) was reported in South Africa[33] and Papua New Guinea (70% for M. hominis and 78% for U. urealyticum ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of M. hominis among women reportedly ranges between 0.6% and 50.4% [12][13][14][15]. Bhatt et al reported a prevalence of 14.2% for M. hominis in women with genital tract infections [16].…”
Section: Isolation Ratementioning
confidence: 99%